The Influence of Globalization on Migration Flows of Indonesian Female Migrant Workers to Saudi Arabia - Josephine Audrey; Fakhri Sabiq Muawal; Eva Firsha (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Globalization has had a broad impact on various aspects of life, including the supporting aspects of the international world order, ranging from social, cultural, political, tourism, to the economy. Globalization also has a significant impact on the occurrence of international migration. This research seeks to highlight the phenomena that occur behind the opening of employment opportunities for women, which on the other hand will also encourage acts of violence, especially against Indonesian female workers in Saudi Arabia. The author uses qualitative research methods with case study techniques to analyze research problems. The author also uses a literature study data collection technique that uses secondary data such as books, journal articles, reports from governments and international organizations and online news as reference sources. The results obtained from this study are that there is an influence between globalization and the migration of Indonesian women workers to Saudi Arabia. There are many positive sides from the influence of globalization such as open access for migrant workers to get jobs and improve life in destination countries. However, there are also negative impacts such as the occurrence of various cases of violence and crimes against female workers, especially against Indonesian women workers in Saudi Arabia.